STUDENT TEAMWORK AS A MEANS OF CREATIVITY EDUCATION (ENTREPRENEURSHIP) - Černevičiūtė, Jūratė; Strazdas, Rolandas; Morkevičius, Vaidas; Jančoras, Žilvinas; Kregždaitė, Rusnė (Acta Paedagogica Vilnensia, 2014)
The article deals with the problems of developing entrepreneurship within the scope of university studies as a personal and collective creativity essential for a modern business developer. The main orientation of an entrepreneur – search for novelties in business – is inevitably accompanied by creativity; therefore, the universities that aim at preparing graduates of the highest qualification are faced with the necessity to foster their students’ creativity and entrepreneurship. Moreover, entrepreneurship is related not only to individual but perhaps even more so with collective creativity which is perceived as an ability to create innovations of systems. With certain characteristic features inherent to the development of students’ collective creativity, proper development methods must be applied. The article presents one of these methods – the collective creativity development model. Furthermore, the article covers also factors of the clarity of a students’ teamwork task, which significantly impact the teamwork results. After determining the influence of possessed knowledge related to the task on the comprehension of the task (task clarity), a creative information search module is introduced, the key function of which is training the teams of students to systematically search for information necessary in order to accomplish teamwork tasks.
Keywords: entrepreneurship; creativity development; teamwork factors; creative information search model